Modelagem de corredores para Callicebus Coimbrai e Callicebus Barbarabrownae, primatas ameaçados no Nordeste brasileiro - George, Giesta Krishna de Saint (2018)
Fragmentation and habitat loss combined with anthropic activities are the most cited causes of biological diversity loss. The reduction of forest habitats results in population’s isolation and a greater extinction risk. Arboreal primates are threatened mainly by fragmentation and habitat loss. We studied two arboreal primate species: Callicebus coimbrai (Primates, Pitheciidae) is endemic to the Northeastern Atlantic Forest Biome, while Callicebus barbarabrownae is endemic to the Caatinga Biome, northeastern Brazil. Both species live in highly isolated fragmented landscapes, occurring in Sergipe and Bahia states. Priority areas had been previously defined by specialists for Callicebus coimbrai (12 areas in Atlantic Forest) and Callicebus barbarabrownae (7 areas in Caatinga). The preset study had as objective to identify possible connection routes, simulating corridors among forest remnants occupied by both species within priority areas. We developed a bibliographic survey (2000-2016) in thesis, dissertations and internet bases to obtain the species’ occurrence points. To simulate corridors, we used a least cost route algorithm. Connections based on these algorithms have never been simulated for these two species. Corridors were simulated on resistance surfaces created on land-use classified images (MapBiomas 2016). Corridors were simulated in all available priority areas. In sum, we simulated 570 corridors (30 replicates for each priority area). A total of 74 fragments were identified for connection in priority areas of C. coimbrai and 36 in priority areas of C. barbarabrownae. The largest land use cover in priority areas in the Atlantic Forest was Agriculture or Pasture (60.37%), while in Caatinga it was Open Forest (52.16%). Priority areas in Caatinga are larger than those in Atlantic Forest. There are more forest fragments in Caatinga than in Mata Atlântica. On the other hand, the Atlantic Forest showed a higher density of forest remnant, indicating higher fragmentation. Ecological corridors had similar length and costs both in Caatinga and Mata Atlântica. In general, Caatinga landscapes are more permeable to the studied species, presenting a larger cover Open Forest. In the Atlantic Forest there is a larger cover of Agriculture or Pasture, which is less permeable. We recommend conservation actions primarily for C. barbarabrownae, which is classified as "critically endangered". For C. coimbrai we recommend stepping stones implementation to the matrix low permeability in which it is inserted.